Mass spectrometric analysis of purine de novo biosynthesis intermediates - Mádrová, Lucie; Krijt, Matyáš; Barešová, Veronika; Václavík, Jan; Friedecký, David; Dobešová, Dana; Součková, Olga; Škopová, Václava; Adam, Tomáš; Zikánová, Marie (PloS one, 2018)
Purines are essential molecules for all forms of life. In addition to constituting a backbone of DNA and RNA, purines play roles in many metabolic pathways, such as energy utilization, regulation of enzyme activity, and cell signaling. The supply of purines is provided by two pathways: the salvage pathway and de novo synthesis. Although purine de novo synthesis (PDNS) activity varies during the cell cycle, this pathway represents an important source of purines, especially for rapidly dividing cells. A method for the detailed study of PDNS is lacking for analytical reasons (sensitivity) and because of the commercial unavailability of the compounds. The aim was to fully describe the mass spectrometric fragmentation behavior of newly synthesized PDNS-related metabolites and develop an analytical method. Except for four initial ribotide PDNS intermediates that preferentially lost water or phosphate or cleaved the forming base of the purine ring, all the other metabolites studied cleaved the glycosidic bond in the first fragmentation stage. Fragmentation was possible in the third to sixth stages. A liquid chromatography-high-resolution mass spectrometric method was developed and applied in the analysis of CRISPR-Cas9 genome-edited HeLa cells deficient in the individual enzymatic steps of PDNS and the salvage pathway. The identities of the newly synthesized intermediates of PDNS were confirmed by comparing the fragmentation patterns of the synthesized metabolites with those produced by cells (formed under pathological conditions of known and theoretically possible defects of PDNS). The use of stable isotope incorporation allowed the confirmation of fragmentation mechanisms and provided data for future fluxomic experiments. This method may find uses in the diagnosis of PDNS disorders, the investigation of purinosome formation, cancer research, enzyme inhibition studies, and other applications.
Keywords: Purines; editace genu; HeLa buňky; tandemová hmotnostní spektrometrie; DNA; CRISPR-Cas systémy; Gene Editing; Chromatography, Liquid; CRISPR-Cas Systems; Tandem Mass Spectrometry; puriny; lidé; RNA; HeLa Cells; Humans; chromatografie kapalinová